Polyethylene glycol plus ascorbic acid for bowel preparation in chronic kidney disease. Issue 36 (September 2016) - Lee, Jae Min; Keum, Bora; Yoo, In Kyung; Kim, Seung Han; Choi, Hyuk Soon; Kim, Eun Sun; Seo, Yeon Seok; Jeen, Yoon Tae; Chun, Hoon Jai; Lee, Hong Sik; Um, Soon Ho; Kim, Chang Duck; et al.
Abstract : Abstract: The safety of polyethylene glycol plus ascorbic acid has not been fully investigated in patients with renal insufficiency. High-dose ascorbic acid could induce hyperoxaluria, thereby causing tubule-interstitial nephritis and renal failure. This study aims to evaluate the safety and efficacy of polyethylene glycol plus ascorbic acid in patients with chronic kidney disease. We retrospectively reviewed prospectively collected data on colonoscopy in patients with impaired renal function. Patients were divided into 2 groups: 2 L polyethylene glycol plus ascorbic acid (n = 61) and 4 L polyethylene glycol (n = 80). The safety of the 2 groups was compared by assessing the differences in laboratory findings before and after bowel cleansing. The laboratory findings were not significantly different before and after the administration of 2 L polyethylene glycol plus ascorbic acid or 4 L polyethylene glycol. In both groups, the estimated glomerular filtration rate was not influenced by the administration of the bowel-cleansing agent. Patients' reports on tolerance and acceptability were better in the 2 L polyethylene glycol plus ascorbic acid group than in the 4 L polyethylene glycol group. The 2 L polyethylene glycol plus ascorbic acid solution is a safe choice for bowel preparation before colonoscopy in patients with impaired renal function.